Protein targets of inflammatory serine proteases and cardiovascular disease - Sharony Ram; Yu Pey-Jen; Park Joy; Galloway Aubrey C; Mignatti Paolo; Pintucci Giuseppe (BMC, 2010)
Abstract Serine proteases are a key component of the inflammatory response as they are discharged from activated leukocytes and mast cells or generated through the coagulation cascade. Their enzymatic activity plays a major role in the body's defense mechanisms but it has also an impact on vascular homeostasis and tissue remodeling. Here we focus on the biological role of serine proteases in the context of cardiovascular disease and their mechanism(s) of action in determining specific vascular and tissue phenotypes. Protease-activated receptors (PARs) mediate serine protease effects; however, these proteases also exert a number of biological activities independent of PARs as they target specific protein substrates implicated in vascular remodeling and the development of cardiovascular disease thus controlling their activities. In this review both PAR-dependent and -independent mechanisms of action of serine proteases are discussed for their relevance to vascular homeostasis and structural/functional alterations of the cardiovascular system. The elucidation of these mechanisms will lead to a better understanding of the molecular forces that control vascular and tissue homeostasis and to effective preventative and therapeutic approaches.